Review on Concepts of Software Testing - Kaur, Sandeep; Kaur, Navdeep; Kaur, Harjeet (IJRDO -Journal of Computer Science Engineering, 2017)
Software testing is any activity aimed at evaluating an attribute or capability of a program or system and determining that itmeets its required results. Although crucial to software quality and widely deployed by programmers and testers, softwaretesting still remains an art, due to limited understanding of the principles of software. The difficulty in software testing stemsfrom the complexity of software: we cannot completely test a program with moderate complexity. Testing is more than justdebugging. The purpose of testing can be quality assurance, verification and validation, or reliability estimation. Testing canbe used as a generic metric as well. Correctness testing and reliability testing are two major areas of testing. Software testingis a trade-off between budget, time and quality.